Health system barriers to hypertension care in Peru: Rapid assessment to inform organizational-level change. - Kendra N Williams; Janeth Tenorio-Mucha; Karina Campos-Blanco; Lindsay J Underhill; Armando Valdés-Velásquez; Antonia Fuentes Herbozo; Laura K Beres; Lisa de las Fuentes; Lucy Cordova-Ascona; Zoila Vela-Clavo; Gonzalo Mariano Cuentas-Canal; Juan Carlos Mendoza-Velasquez; et al. (Public Library of Science (PLoS), 2024)
Traditional patient- and provider-level hypertension interventions have proven insufficient to halt hypertension as the leading cause of morbidity and mortality globally. Systems-level interventions are required to address factors challenging hypertension control across a social ecological framework, an under-studied topic particularly salient in low- and middle-income countries (LMICs) such as Peru. To inform such interventions, we sought to identify key health systems barriers to hypertension care in Puno, Peru. A participatory stakeholder workshop (October 2021) and 21 in-depth interviews (October 2021-March 2022) were conducted with 55 healthcare professionals (i.e., doctors, nurses, midwives, dentists, nutritionists), followed by a deductive qualitative analysis of transcripts and notes. Participating healthcare providers indicated that low prioritization and lack of national policies for hypertension care have resulted in limited funding and lack of societal-level prevention efforts. Additionally, limited cultural consideration, both in national guidelines as well as by some providers in Puno, results in inadequate care that may not align with local traditions. Providers highlighted that patient care is also hampered by inadequate distribution and occasional shortages of medications and equipment, as well as a lack of personnel and limited opportunities for training in hypertension. Multiple incompatible health information systems, complicated referral systems, and geographic barriers additionally hinder continuity of care and care seeking. Insights gained from health providers on the healthcare system in Puno provide essential contextual information to inform development of organizational-level strategies necessary to improve provider and patient behaviors to achieve better hypertension care outcomes.